Bismuth Telluride nanocrystal: broadband nonlinear response and its application in ultrafast photonics - Jiang, Guobao (Sci Rep, 2018)
We come up with a hybrid liquid exfoliation method to prepare bismuth telluride nanocrystals efficiently and cost-effectively. The nonlinear transmittance of the nanocrystals has been characterized with Z-scan technique, which can manifest its broadband saturable absorption behavior experimentally. The as-fabricated nanocrystals were integrated onto fiber end facet to form a fiber compatible nonlinear absorption device with optical deposition method, which was then used to modulate the fiber laser with different cavity configurations to deliver pulsed laser successfully. The noise-like pulse and dissipative soliton have been obtained with wavelength centered at 1562 nm and 1068 nm, respectively. These results confirm the effectiveness of the hybrid liquid exfoliation method to prepare bismuth telluride into nanocrystals, and the broadband nonlinear optical response and ultrafast photonics application potential of the nanocrystals.